The importance of Re Takaful in risk management/ Siti Hawa Mohd - Mohd., Siti Hawa (2019)
Early during the Prophet era, Takaful operation have been implemented between all the tribe in Mecca. It is done as a process to prevent and decrease all the risks and catastrophe that may happen. Now, all over the world, it is known as Takaful operation. Takaful operations played an important part in Muslim's life. Despites Takaful industry has been developing in recent years it still facing ^ few difficulties and challenges. As Takaful company provide protection and risk sharing" to the contributors, who give protection and risk sharing to the Takaful company. Thus, the need of security and protection for Takaful company to operate efficiently. As in insurance, reinsurance played a big part in preparing and reducing risk of their operation. It also goes to Takaful operation, Re Takaful operation also significant and important to the Takaful company for them to operate efficiently as Re Takaful operation is a service that work as mitigating tools. Besides Re Takaful operation will also affect Takaful company in many aspects such as company rating and reducing solvency risk. Lastly, Re Takaful operation, is an important part "of Takaful industry because it will help Muslim and provide choice to all the Muslim as it is vital for Muslim to perform their activities according to the Islamic religion.